PENGARUH PENGELOLAAN LAPORAN KEUANGAN, MODAL KEUANGAN DAN PENGGUNAAN INFORMASI AKUNTANSI TERHADAP KINERJA KEUANGAN UMKM DI DAERAH KOTA KUPANG - Bouk, Theresia; Hasim As'ari (ITB AAS Indonesia Surakarta, 2025)
This study aims to determine the Influence of Financial Report Management, Financial Capital and Use of Accounting Information on the Financial Performance of MSMEs in Kupang City. The sample size is determined through the Slovin formula, which produces a sample size of 52 MSMEs. The data source consists of primary data. The data collection method is carried out by distributing questionnaires. The data analysis method used is multiple linear regression testing. Data analysis uses SPSS version 26.0 for Windows. The results of this study indicate that: (1) financial report management does not affect the financial performance of MSMEs in Oebobo District; (2) financial capital has a positive and significant effect on the financial performance of MSMEs in Oebobo District; (3) the use of accounting information has a positive and significant effect on the financial performance of MSMEs in Oebobo District